2011
DOI: 10.1113/jphysiol.2011.216978
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physiological measures of excitability and levels of glutamate and GABA in the human motor cortex

Abstract: Non-technical summaryInter-individual differences in regional GABA as assessed by magnetic resonance spectroscopy (MRS) relate to behavioural variation in humans. However, it is not clear what the relationship is between MRS measures of the concentration of neurotransmitters in a region and synaptic activity. Transcranial magnetic stimulation (TMS) techniques provide physiological measures of cortical excitation or inhibition. Here, we investigated the relationship between MRS and TMS measures of glutamatergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
247
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(281 citation statements)
references
References 34 publications
(73 reference statements)
17
247
6
1
Order By: Relevance
“…By temporally resolving cortical responses to each TMS pulse, we demonstrate that starting from the initial "basin of suppression," consecutive TMS pulses (10 Hz) produce a stepwise buildup of activity, reaching signal levels that suggest massive spiking across large populations of neurons. These results promote the view that subsequent TMS pulses, each within a 100-ms time window, weaken inhibitory drive (57) and activate excitatory circuits that outbalance inhibition involving NMDAreceptor activation (61), overall leading to an excitatory state of the cortex (62).…”
Section: Discussionmentioning
confidence: 81%
“…By temporally resolving cortical responses to each TMS pulse, we demonstrate that starting from the initial "basin of suppression," consecutive TMS pulses (10 Hz) produce a stepwise buildup of activity, reaching signal levels that suggest massive spiking across large populations of neurons. These results promote the view that subsequent TMS pulses, each within a 100-ms time window, weaken inhibitory drive (57) and activate excitatory circuits that outbalance inhibition involving NMDAreceptor activation (61), overall leading to an excitatory state of the cortex (62).…”
Section: Discussionmentioning
confidence: 81%
“…SICI at 1 millisecond correlated with GABA concentration measured by magnetic resonance spectroscopy. 27 We found that there was decreased SICI at the midrange of S1 intensities in patients with PD. The results were similar to the SICI tested at SICF trough 1, suggesting that impaired GABA-mediated inhibition may be responsible.…”
mentioning
confidence: 76%
“…A magnetic resonance spectroscopy study by Stagg and colleagues (2011a) revealed that tDCS (1mA, 10min) with the anode placed over M1 reduces local GABA concentration and tDCS with the cathode placed over M1reduces glutamatergic activity. In a subsequent study, Stagg and colleagues (2011b) found significant correlations between GABA concentration level and 1 ms ISI SICI which is thought to reflect extrasynaptic GABA tone (Stagg et al 2011b) as well as corticospinal excitability and glutamate level. However, there was no association between GABA concentration level and SICI with 2.5 ms ISI which is thought to reflect synaptic GABAA activity.…”
Section: Neurophysiological Effects Of Tdcs With the Cathode Placed Omentioning
confidence: 95%